Characterization of the Glehnia littoralis Non-specific Phospholipase C Gene GlNPC3 and Its Involvement in the Salt Stress Response - Li, Li; Li, Naiwei; Qi, Xiwu; Bai, Yang; Chen, Qiutong; Fang, Hailing; Yu, Xu; Liu, Dongmei; Liang, Chengyuan; Zhou, Yifeng (Frontiers in Plant Science, 2021)
Glehnia littoralis is a medicinal halophyte that inhabits sandy beaches and has high ecological and commercial value. However, the molecular mechanism of salt adaptation in G. littoralis remains largely unknown. Here, we cloned and identified a non-specific phospholipase C gene (GlNPC3) from G. littoralis, which conferred lipid-mediated signaling during the salt stress response. The expression of GlNPC3 was induced continuously by salt treatment. Overexpression of GlNPC3 in Arabidopsis thaliana increased salt tolerance compared to wild-type (WT) plants. GlNPC3-overexpressing plants had longer roots and higher fresh and dry masses under the salt treatment. The GlNPC3 expression pattern revealed that the gene was expressed in most G. littoralis tissues, particularly in roots. The subcellular localization of GlNPC3 was mainly at the plasma membrane, and partially at the tonoplast. GlNPC3 hydrolyzed common membrane phospholipids, such as phosphotidylserine (PS), phosphoethanolamine (PE) and phosphocholine (PC). In vitro enzymatic assay showed salt-induced total NPC activation in A. thaliana GlNPC3-overexpressing plants. Plant lipid profiling showed a significant change in the membrane-lipid composition of A. thaliana GlNPC3-overexpressing plants compared to WT after the salt treatment. Furthermore, downregulation of GlNPC3 expression by virus-induced gene silencing in G. littoralis reduced the expression levels of some stress-related genes, such as SnRK2, P5SC5, TPC1, and SOS1. Together, these results indicated that GlNPC3 and GlNPC3-mediated membrane lipid change played a positive role in the response of G. littoralis to a saline environment.